2015
DOI: 10.1089/lap.2015.0077
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Recurrence and Quality of Life Assessment Using the Hernia-Specific Carolinas Comfort Scale Following Laparoscopic Inguinal Hernia Repair

Abstract: Patient-reported medium-term symptoms following laparoscopic inguinal hernia repair appear common; however, the prevalence of severe or disabling symptoms is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Jalil et al 1 have reported on the medium-term quality of life outcomes of patients undergoing inguinal hernia repair using a laparoscopic transabdominal preperitoneal (TAPP) approach and a validated, hernia-specific questionnaire. Although the reported prevalence of severe or disabling symptoms following TAPP inguinal hernia repair seems to be low, the numbers of patients reporting mild to moderate pain, movement limitations, and sensation of mesh are likely much higher than many of us care to admit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jalil et al 1 have reported on the medium-term quality of life outcomes of patients undergoing inguinal hernia repair using a laparoscopic transabdominal preperitoneal (TAPP) approach and a validated, hernia-specific questionnaire. Although the reported prevalence of severe or disabling symptoms following TAPP inguinal hernia repair seems to be low, the numbers of patients reporting mild to moderate pain, movement limitations, and sensation of mesh are likely much higher than many of us care to admit.…”
mentioning
confidence: 99%
“…Although recurrence will always be an important outcome measure for hernia repair, we are now becoming more in tune with the implications of hernia repair on our patient's quality of life. The work by Jalil et al 1 and others is a huge first step in evaluating important quality of life outcomes in our hernia patients so that we can quantify the problem and hopefully find ways to impact it in a positive way.…”
mentioning
confidence: 99%